Fabrication and testing of a poly(vinylidene fluoride) (PVDF) microvalve for gas flow control - Wiederkehr, Rodrigo S.; Salvadori, Maria C.; Brugger, Juergen; Degasperi, Francisco T. [UNESP]; Cattani, Mauro (Iop Publishing Ltd, 2007)
A microactuator made from poly(vinylidene fluoride) (PVDF), a piezoelectric polymer, was fabricated to control the gas flow rate through a glass micronozzle. The actuator was formed by gluing together two PVDF sheets with opposite polarization directions. The sheets were covered with thin conducting films on one side, that were then used as electrodes to apply an electric field to move the valve. The actuator has a rectangular shape, 3 mm x 6 mm. The device was incorporated with a micronozzle fabricated by a powder blasting technique. Upon applying a DC voltage across the actuator electrodes, one sheet expands while the other contracts, generating an opening motion. A voltage of +300 V DC was used to open the device by moving the actuator 30 mu m, and a voltage of -200 V DC was used to close the device by moving the actuator 20 mu m lower than the relaxed position. Flow measurements were performed in a low-pressure vacuum system, maintaining the microvalve inlet pressure constant at 266 Pa. Tests carried out with the actuator in the open position and with a pressure ratio (inlet pressure divided by outlet pressure) of 0.5, indicated a flow rate of 0.36 sccm. In the closed position, and with a pressure ratio of 0.2, a flow rate of 0.32 sccm was measured.